Knowledge and practice related to Covid-19 among mentally ill patients of psychiatric OPD at BP Koirala Institute of Health Sciences, Dharan - Rai, Bhumika; Pradhan, Nirmala; Lama, Sami; Thapa, Kriti; Pokharel, Rita; Limbu, Suren (Journal of Psychiatrists' Association of Nepal, 2024)
Introduction: The covid-19 pandemic has caused a serious impact on both the physical and mental health of mentally ill population. Mentally ill individuals are vulnerable to easy transmission of infection compared to the general population. The objective of the study is to assessthe level of Knowledge and Practice related to Covid-19 among mental ill patients. Material & Methods: A cross-sectional study was conducted among psychiatric patients attending Psychiatric out-patient department of BPKIHS. Non-probability purposive sampling was used to collect information from 147 respondents. Data was collected through face-to-face interview using self-developed questionnaires on knowledge and practice related to Covid-19. Descriptive analysis and chi-square were used to find the association of knowledge and practice with selected demographic variables and Pearson’s correlation was used to assess the correlation between knowledge and practice. Results: Out of 147 mentally ill patients, the mean age was 37.54 years (SD= 37.54±13.053), 51.7% were female, 64.6% were married, 9.5% were illiterate, and 7.5% were infected with Covid-19. More than three fourth (89.8%) of them scored Good level of knowledge and 95.9% had a Good level of practice regarding Covid-19. The level of knowledge showed a significant association with patients’ education and occupational status and a positive correlation between knowledge and practice. Conclusion: The study result showed that mentally ill patients had a good level of knowledge and practice towards COVID-19. The level of knowledge showed a significant association with education and occupation.